Sheep genetic diversity in Bhutan using microsatellite markers - Tashi, D.; Wafula, P.; Yoshio, Y.; Shinji, S.; Kenji, O.; Hanotte, Olivier H.; Bang-Zhong, L.; Hideyuki, M.; Han Jianlin (Wiley, 2010)
Genotype data from eight microsatellite markers were used to assess genetic diversity and relationships among five indigenous Bhutanese sheep populations, Sakten, Jakar, Sarpang, Sipsu and Tsirang. Estimates of mean observed and expected heterozygosities, mean number of alleles per locus/population were obtained. The highest observed heterozygosities were found in Jakar (0.657) and Sakten (0.647), while the lowest one was found in Tsirang (0.539). Genetic distances, pairwise proportion of different alleles, UPGMA tree, and principal component analysis indicate close relationship among Tsirang, Sipsu and Sarpang populations, while Jakar and Sakten populations are located in one cluster. These two clusters are separated geographically, and show distinct phenotypic as well as molecular characters. We therefore recommend that the Bhutanese native sheep populations be classified into at least two distinct breeds, Jakar-Sakten sheep and Sipsu sheep. Since Jakar and Sakten sheep have different morphological phenotypes, further analyses will be required to understand the genetic differences between these two sheep populations.